Nasal immunization with Lactococcus lactis expressing the pneumococcal protective protein A induces protective immunity in mice - Medina, Marcela Susana (2008)
Nisin-controlled gene expression was used to develop a recombinant strain of Lactococcus lactis that is able to express the pneumococcal protective protein A (PppA) on its surface. Immunodetection assays confirmed that after the induction with nisin, the PppA antigen was predictably and efficiently displayed on the cell surface of the recombinant strain, which was termed L. lactis PppA. The production of mucosal and systemically specific antibodies in adult and young mice was evaluated after mice were nasally immunized with L. lactis PppA. Immunoglobulin M (IgM), IgG, and IgA anti-PppA antibodies were detected in the serum and bronchoalveolar lavage fluid of adult and young mice, which showed that PppA expressed in L. lactis was able to induce a strong mucosal and systemic immune response. Challenge survival experiments demonstrated that immunization with L. lactis PppA was able to increase resistance to systemic and respiratory infection with different pneumococcal serotypes, and passive immunization assays of naïve young mice demonstrated a direct correlation between anti-PppA antibodies and protection. The results presented in this study demonstrate three major characteristics of the effectiveness of nasal immunization with PppA expressed as a protein anchored to the cell wall of L. lactis: it elicited cross-protective immunity against different pneumococcal serotypes, it afforded protection against both systemic and respiratory challenges, and it induced protective immunity in mice of different ages.